Report of a policy dialogue workshop on open source seed systems for climate change adaptation in East Africa - Otieno, Gloria Atieno; Recha, Tobias; Vernooy, Ronnie; Fadda, Carlo; Gebrehawaryat Kidane, Yosef; Halewood, Michael (Bioversity International and the International Center for Tropical Agriculture, 2020)
The report gives a summary of a policy workshop that was held in December 2019 to discuss the complex issues related to access to and use of genetic resources for climate change adaptation. In particular, the workshop focussed on policies to support the further use in research and breeding, or possible ‘direct use in cultivation’ of materials that performed well in participatory trials supported by these projects. The workshop brought together practitioners from Ethiopia, Kenya, Tanzania and Uganda from various non-governmental organizations (NGOs) and advocacy groups, policy makers from government departments, seed inspection and certification services and researchers and breeders.